The joint impact of temperature, humidity, and air pollution on COVID-19 incidence: a multi-country time-series study in 439 cities - Keita Wagatsuma; Denise Feurer; Wenhua Yu; Rongbin Xu; Tim Riffe; Maxi Stella Kniffka; Enrique Acosta; Ben Armstrong; Malcolm Mistry; Rachel Lowe; Dominic Royé; Masahiro Hashizume; et al. (My University, 2026)
independently increased COVID-19 incidence, highlighting the need to consider both thermal environment and air quality when designing climate-resilient public health responses. These findings enhance understanding of how climate-related environmental stressors influence COVID-19 transmission.
Keywords: Environmental science; Air pollution; Environmental health; Particulates; Air quality index; Lag; Confidence interval; Effect modification; Relative risk; Distributed lag; Generalized additive model; Climate change; Stressor; Pollution; Air temperature; Coronavirus disease 2019 (COVID-19); Health effect; Environmental engineering; Public health; Exposure assessment; Joint (building); Cumulative effects; Multilevel model; Meteorology; Environmental protection; Environmental quality; Product (mathematics); Risk assessment; Random effects model; Incidence (geometry); Apparent temperature; Geography; Interaction; Transmission (telecommunications); Environmental impact assessment; Term (time); Air pollutants; Air pollution; Particulates; Air quality index; Lag; Confidence interval; Effect modification; Relative risk; Distributed lag; Generalized additive model; Climate change; COVID-19 epidemiology; COVID-19 epidemiology; COVID-19 epidemiology; SARS-CoV-2; SARS-CoV-2; SARS-CoV-2; Air Pollutants; Air Pollutants; Air Pollutants analysis; Air Pollution adverse effects; Air Pollution adverse effects; Air Pollution statistics & numerical data; Air Pollution statistics & numerical data; Air Pollution statistics & numerical data; Cities epidemiology; Cities epidemiology; Cities epidemiology; Environmental Exposure; Humans; Humans; Humans; Humidity; Humidity; Humidity; Temperature; Temperature; Temperature; Incidence; Incidence; Incidence; Particulate Matter analysis; Particulate Matter analysis; Particulate Matter analysis; Pandemics; Physical Sciences Mathematics Modeling and Simulation COVID-19 epidemiological studies; Physical Sciences Environmental Science Global and Planetary Change COVID-19 impact on air quality; Health Sciences Medicine Infectious Diseases COVID-19 Clinical Research Studies